Changes in Air Pollutants from Fireworks in Chinese Cities - Yonghang Lai; Peter Brimblecombe (Atmosphere, 2022)
Chinese New Year has traditionally been welcomed with fireworks, but this has meant this holiday can experience intense peaks of pollutants, particularly as particulate matter. Such environmental issues add to other risks (e.g., accident, fire, and ecological and health threats) posed by firework displays, but cultural reasons encourage such celebrations. This study examines air pollution from fireworks across a time of increasingly stringent bans as a time series from 2014–2021 using a random forest (decision-tree) model to explore the effect of year-to-year weather changes on pollutant concentrations at Chinese New Year. Peak concentrations of firework pollutants have decreased in cities and hint at the importance of well-enforced regulation of these traditional celebrations, e.g., Beijing, Tianjin, and Chongqing. The model suggested relative humidity was an important controlling variable, perhaps as the presence of water vapor might also accelerate particle growth but also as a surrogate parameter related to atmospheric mixing. Bans on fireworks, resisted at first, have shown evidence of growing public acceptance. The regulations are increasingly effective, even in the outer parts of cities. Celebrations might safely return as public firework displays, including light shows and the use of lanterns.